SOSIALISASI BAHAYA PINJAMAN ONLINE ILEGAL DI DESALOPOK KABUPATEN SUMBAWA - Muhammad Rizqi, Reza; Zulfikar Akbar, Arya; Hardiansyah, Rian (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
The development of financial technology (fintech) in Indonesia has opened up wider access to credit, but this has been accompanied by the rise of illegal online lending practices that are disturbing and harmful to the community. Rural communities, such as in Lopok Village, Sumbawa Regency, face unique vulnerabilities amid uneven digital penetration and financial literacy gaps, despite provincial statistics showing high literacy rates. In response to this issue, a community service team from the Faculty of Economics and Business, Sumbawa University of Technology (FEB UTS) implemented an outreach program aimed at increasing the understanding and awareness of the Lopok Village community regarding the dangers of illegal online lending. The activity employed participatory education methods, including lectures, discussions, and case studies, with program effectiveness evaluated through pre-test and post-test approaches. The evaluation results showed a significant increase in participants' knowledge across all measured indicators, including the ability to distinguish between legal and illegal online loans, awareness of the risks of personal data misuse, and knowledge of official complaint channels. This activity proves that targeted and contextual socialization is an effective empowerment strategy to protect rural communities from the threat of digital financial crime.